Cotrimoxazole-Induced Hypoglycaemia in a Patient with Churg-Strauss Syndrome. (8th September 2013) - Senanayake, Russell; Mukhtar, Mamoun
Abstract : Cotrimoxazole is a commonly used antimicrobial agent which is traditionally indicated in the management of pneumocystis infection of which HIV and immunosuppressed individuals are at high risk. Furthermore, it can be used on the long term for prophylactic indications. Hypoglycaemia following commencement of cotrimaoxazole is a rare adverse effect which was first described in 1988. We describe a case of hypoglycaemia shortly following initiation of cotrimoxazole indicated as long-term prophylaxis on a background of Churg-Strauss syndrome. The patient was symptomatic for hypoglycaemia despite simultaneous use of high-dose prednisolone; however, the hypoglycaemia did not require a hospital admission. We will explore the risk factors, monitoring requirements, and the mechanism by which co-trimoxazole induces hypoglycaemia.